2020
DOI: 10.1371/journal.pone.0229625
|View full text |Cite
|
Sign up to set email alerts
|

As cold as a fish? Relationships between the Dark Triad personality traits and affective experience during the day: A day reconstruction study

Abstract: The Dark Triad of personality is a cluster of three socially aversive personality traits: Machiavellianism, narcissism and psychopathy. These traits are associated with a selfish, aggressive and exploitative interpersonal strategy. The objective of the current study was to establish relationships between the Dark Triad traits (and their dimensions) and momentary affect. Machiavellianism, grandiose narcissism, vulnerable narcissism and the dimensions of the Triarchic model of psychopathy (namely, boldness, mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 152 publications
(206 reference statements)
0
10
0
Order By: Relevance
“…Under some circumstances, Machiavellianism can positively impact the organizations because high Mach employees find it beneficial to adapt their behavior to benefit the organization (Belschak et al, 2018) and demonstrate better task performance (Kuyumcu and Dahling, 2014). Besides, this study adds to a growing body of research (Pilch, 2020), indicating a less opinionated perspective about the Dark Triads, like Machiavellianism. On the other hand, resilience has a mediating role between self-concept and employee performance, and this mediating role has been empirically supported by recent research (Labrague and De Los Santos, 2021) 5.3.2 Practical implications.…”
Section: Limitationsmentioning
confidence: 77%
“…Under some circumstances, Machiavellianism can positively impact the organizations because high Mach employees find it beneficial to adapt their behavior to benefit the organization (Belschak et al, 2018) and demonstrate better task performance (Kuyumcu and Dahling, 2014). Besides, this study adds to a growing body of research (Pilch, 2020), indicating a less opinionated perspective about the Dark Triads, like Machiavellianism. On the other hand, resilience has a mediating role between self-concept and employee performance, and this mediating role has been empirically supported by recent research (Labrague and De Los Santos, 2021) 5.3.2 Practical implications.…”
Section: Limitationsmentioning
confidence: 77%
“…The specific dark triad empathic difficulties (Jonason & Krause, 2013) may explain the preference for utilitarian strategies when individuals high in Machiavellianism or narcissism face moral dilemmas. Some studies have concluded that individuals with dark triad traits might display higher cognitive empathy abilities compared to affective empathy competencies (Pilch, 2020;Wai & Tiliopoulos, 2012). This means that individuals high in these negative personality traits may possess an empathic profile that allows them to read and evaluate others' emotions and then use this sensitive information to manipulate and explore people and get what they want from them, while a diminished affective empathy might lead them to ignore possible damages inflicted in the process.…”
Section: Discussionmentioning
confidence: 99%
“…Scientists of evolutionary psychology stated that dark triad traits remained because they were valuable for people in order to survive and adapt (Pilch, 2020). Research results have already confirmed that people with dark triad traits have a high need for power and succeed to become leaders in organisations (Jonason et al, 2012;Krick et al, 2016).…”
Section: Combination Of Dark Triad Traits and Transformational Leader...mentioning
confidence: 97%